Anti-oxidation coating of SiCf / Ti3Al composite fastener and preparation method of anti-oxidation coating
By depositing a high-entropy silicon borode coating on the surface of SiCf/Ti3Al composite fasteners, the problem of insufficient oxidation resistance at high temperatures is solved, and higher oxidation resistance and toughness are achieved, and high-temperature oxidation erosion is effectively dealt with.
Patent Information
- Application Number
- CN202411896487.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
SiCf/Ti3Al composite materials are susceptible to oxidation and corrosion in high temperature environments. The existing silicide ceramic coatings have poor fluidity at high temperatures and cannot effectively repair cracks and holes, resulting in insufficient oxidation resistance.
High-entropy silicon boronide is used as the antioxidant coating material, and a high-entropy silicon boronide coating is deposited on the surface of SiCf/Ti3Al composite fastener through magnetron sputtering technology. A dense SiO2 oxide layer is formed by using preferential oxidation of Si atoms and high flowability of B2O3 to repair cracks and holes generated during high-temperature oxidation.
It improves the antioxidant performance of SiCf/Ti3Al composite fasteners at high temperatures, enhances the toughness and high temperature stability of the coating, effectively prevents oxygen penetration, and extends the service life of the material.
Smart Images

Figure CN119710587A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high entropy materials and specifically relates to a SiC f Anti-oxidation coating of / Ti3Al composite fasteners and preparation method thereof. Background Art
[0002] Ti-Al intermetallic compounds have many excellent properties, such as high strength and elastic modulus and good high-temperature creep resistance, etc. Among them, Ti3Al alloy is one of the most widely used Ti-Al intermetallic compounds. Ti3Al alloy can be used as an excellent high-temperature structural material for a long time in the temperature range of 600-800℃, but when serving in a high-temperature environment above 800℃, non-protective metal oxide TiO2 is easily generated on the surface of the Ti3Al matrix. These oxidation products make it difficult to form a dense and continuous Al2O3 oxide layer on the surface, which makes the oxidation resistance of the Ti3Al matrix worse and thus suffers from severe oxidation corrosion, limiting the SiC f Application of / Ti3Al composite materials in high temperature environment.
[0003] Coating technology is a surface modification technology that uses coatings to block external oxygen and prevent the protected substrate from being corroded. Among them, silicide ceramic coatings are a hot topic in research and application. Their oxidation resistance mainly comes from the reaction between silicon and oxygen to form a continuous and dense SiO2 oxide layer on the coating surface, thereby preventing further corrosion of the interior by oxygen. At the same time, the fluidity of SiO2 at high temperatures can make up for the cracks and holes generated on the surface of the coating when it is oxidized.
[0004] However, silicide ceramic coatings also have some defects. For example, when the ambient temperature is below 1000℃, the SiO2 glass generated on the surface of the coating during oxidation has a high viscosity and poor fluidity, which limits its ability to heal cracks and pores. In addition, silicide has the problems of high brittleness and poor toughness. Therefore, it cannot meet the requirements of SiC f / Ti3Al composite fasteners' oxidation resistance requirements at high temperatures. Summary of the invention
[0005] The present invention aims to provide a SiC f / Ti3Al composite fastener anti-oxidation coating and preparation method thereof, the high entropy silicon boride provided by the present invention has excellent toughness, high temperature stability and high temperature oxidation resistance, and can meet the requirements of SiC f / Ti3Al composite fasteners' oxidation resistance requirements at high temperatures.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a high entropy silicon boride, comprising metal elements and non-metal elements; the metal elements include Zr, Nb, Mo and W; the non-metal elements include Si and B;
[0008] The molar ratio of the metal element to the non-metal element is 1:1.5-2;
[0009] The molar ratio of Zr, Nb, Mo and W is 5-40:5-40:5-40:5-40;
[0010] The atomic content of B in the non-metallic element is 5 to 25 at.%.
[0011] The present invention also provides a method for preparing the high entropy silicon boride described in the above technical solution, comprising the following steps:
[0012] In an argon environment, a composite target is deposited on a substrate surface by magnetron sputtering to obtain the high entropy silicon boride; the material of the composite target includes MoSi2, WSi2 and NbSi2, and also includes two or more of ZrSi2, ZrB2 and SiB6.
[0013] Preferably, the composite target is composed of 3 to 5 groups of target materials; each group of target materials independently includes 5 to 6 small target materials; each group of target materials independently includes MoSi2 target, WSi2 target and NbSi2 target, and also includes two or more of ZrSi2 target, ZrB2 target and SiB6 target.
[0014] Preferably, the conditions of the magnetron sputtering include: working pressure of 0.6Pa to 1.2Pa, bias voltage of -50 to -150V, number of target positions of 2 to 4, and distance between substrate and composite target of 8 to 12cm; the magnetron sputtering uses a DC power supply, sputtering voltage of 200 to 500V, and sputtering current of 0.6 to 2A.
[0015] Preferably, the temperature of the substrate is 350-650°C.
[0016] The present invention also provides a SiC f / Ti3Al composite fasteners, including SiC f / Ti3Al composite fastener substrate and deposited on the SiC f / Ti3Al composite fastener substrate surface anti-oxidation coating; the material of the anti-oxidation coating is the high entropy silicon boride described in the above technical solution or the high entropy silicon boride obtained by the preparation method described in the above technical solution.
[0017] Preferably, the thickness of the anti-oxidation coating is 2-5 μm.
[0018] The present invention also provides the high entropy silicon boride described in the above technical solution, the high entropy silicon boride obtained by the preparation method described in the above technical solution, or the SiC f Application of Ti3Al composite fasteners in aerospace materials.
[0019] The invention provides a high entropy borosilicate, comprising metal elements and non-metal elements; the metal elements include Zr, Nb, Mo and W; the non-metal elements include Si and B; the molar ratio of the metal elements and the non-metal elements is 1:1.5-2; the molar ratio of Zr, Nb, Mo and W is 5-40:5-40:5-40:5-40; the atomic content of B in the non-metal elements is 5-25 at.%. On the basis of multi-component high entropy silicide, the invention introduces B element to form high entropy borosilicate, in which Si atoms are preferentially oxidized in a high temperature environment, and a dense SiO2 oxide layer is generated on the surface, thereby preventing oxygen from further penetrating into the interior. Moreover, the high-temperature oxidation product of element B, B2O3, can combine with SiO2 glass to form a borosilicate (SiO2·B2O3) glass phase, which has low viscosity and high fluidity. It can not only form a continuous and dense oxide layer on the surface more quickly, but also repair the cracks and holes generated on the surface during the high-temperature oxidation process. The metal elements are all refractory alloy elements and have better stability at high temperatures. At the same time, the toughness of high-entropy silicon boride is significantly improved compared to high-entropy silicide. The high-entropy silicon boride provided by the present invention meets the requirements of SiC as a coating material. f / Ti3Al composite fasteners’ anti-oxidation requirements when serving in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 This is a schematic diagram of the splicing method of the composite target of the present invention;
[0022] Figure 2 This is a schematic diagram of preparing an anti-oxidation coating by magnetron sputtering according to the present invention;
[0023] Figure 3 The SiC with the anti-oxidation coating deposited in Examples 1 to 2 f / Ti3Al composite fastener, the Ti3Al sheet obtained in Comparative Example 1, and the SiC deposited with high entropy silicide coating obtained in Comparative Example 2 fCross-sectional SEM images of the / Ti3Al composite fastener after high temperature oxidation test, wherein a corresponds to Example 1, b corresponds to Example 2, c corresponds to Example 1, and d corresponds to Example 2;
[0024] Figure 4 The SiC with the anti-oxidation coating deposited in Examples 1 to 2 f / Ti3Al composite fastener, the Ti3Al sheet obtained in Comparative Example 1, and the SiC deposited with high entropy silicide coating obtained in Comparative Example 2 f Surface SEM images of the / Ti3Al composite fastener after high temperature oxidation test, wherein a corresponds to corresponding example 1, b corresponds to corresponding example 2, c corresponds to example 1, and d corresponds to example 2;
[0025] Figure 5 The SiC with the anti-oxidation coating deposited in Examples 1 to 2 f / Ti3Al composite fastener and SiC deposited high entropy silicide coating obtained in Comparative Example 2 f Surface SEM images of the / Ti3Al composite fastener after indentation test, where a corresponds to Example 2, b corresponds to Example 1, and c corresponds to Example 2. DETAILED DESCRIPTION
[0026] The present invention provides a high entropy silicon boride, comprising metal elements and non-metal elements; the metal elements include Zr, Nb, Mo and W; the non-metal elements include Si and B;
[0027] The molar ratio of the metal element to the non-metal element is 1:1.5-2;
[0028] The molar ratio of Zr, Nb, Mo and W is 5-40:5-40:5-40:5-40;
[0029] The atomic content of B in the non-metallic element is 5 to 25 at.%.
[0030] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0031] In the present invention, the molar ratio of the metal element to the non-metal element is 1:1.5-2, and in a specific embodiment, it can be 1:2.
[0032] In the present invention, the molar ratio of Zr, Nb, Mo and W is 5-40:5-40:5-40:5-40, and in a specific embodiment, it can be 20:10:10:10 or 20:35:35:35.
[0033] In the present invention, the atomic content of B in the non-metallic element is 5 to 25 at. %, and in a specific embodiment, it can be 15 at. %.
[0034] Compared with traditional silicide coatings, high entropy silicide coatings have high melting points and good thermal stability. During oxidation, Si atoms are preferentially oxidized, which avoids the occurrence of a single metal oxide destroying the dense oxide layer, thereby causing oxidation protection failure. Therefore, high entropy silicide coatings are more likely to form a continuous and dense SiO2 oxide layer on the surface, thereby improving the overall oxidation resistance of the coating. In order to further improve its oxidation resistance and mechanical properties, the present invention introduces B elements to form high entropy silicon boride on the basis of multi-component high entropy silicide. In a high temperature environment, Si atoms therein are preferentially oxidized, and a dense SiO2 oxide layer is generated on the surface, which hinders oxygen from further penetrating into the interior. And the product of high-temperature oxidation of boron elements, B2O3, can be combined with SiO2 glass to form a borosilicate (SiO2·B2O3) glass phase, which has low viscosity and high fluidity, and has good crack healing ability. It can not only form a continuous and dense oxide layer on the surface faster, but also can repair cracks and holes generated on the surface during high-temperature oxidation, and can effectively prevent oxygen penetration; the metal elements are all refractory alloy elements, and have better stability at high temperatures. At the same time, the toughness of high entropy silicon boride is significantly improved compared with high entropy silicide. The high entropy silicon boride provided by the present invention meets the requirements of SiC as a coating material. f / Ti3Al composite fasteners’ anti-oxidation requirements when serving in high temperature environments.
[0035] The present invention also provides a method for preparing the high entropy silicon boride described in the above technical solution, comprising the following steps:
[0036] In an argon environment, a composite target is deposited on the surface of a substrate by magnetron sputtering to obtain the high entropy silicon boride coating; the material of the composite target includes MoSi2, WSi2 and NbSi2, and also includes two or more of ZrSi2, ZrB2 and SiB6.
[0037] In the present invention, the composite target is composed of 3 to 5 groups of target materials, and in a specific embodiment, it can be 3 groups or 4 groups; each group of target materials independently includes 5 to 6 small targets; each group of target materials independently includes MoSi2 target, WSi2 target and NbSi2 target, and also includes two or more of ZrSi2 target, ZrB2 target and SiB6 target, and in a specific embodiment, it can be MoSi2 target, WSi2 target, NbSi2 target, ZrSi2 target and ZrB2 target; the arrangement order of small targets in each group of target materials can be the same; the small targets are independently rectangular targets, and the specifications are independently 10 to 15 mm × 75 to 100 mm × 8 to 10 mm, and in a specific embodiment, they can be 10 mm × 75 mm × 8 mm or 12 mm × 80 mm × 8 mm.
[0038] In the present invention, the substrate is placed on a sample holder; the sample holder can rotate while cooperating with the main shaft to revolve; the rotation rate of the substrate is 3 to 10 r / min, and in a specific embodiment, it can be 5 r / min or 8 r / min; the rotation rate is 2 to 5 r / min, and in a specific embodiment, it can be 2 r / min or 3 r / min.
[0039] In the present invention, the magnetron sputtering may also include cleaning and drying in sequence; the cleaning includes pickling and ultrasonic cleaning in sequence; the pickling reagent is a hydrofluoric acid solution; the mass percentage concentration of the hydrofluoric acid solution is 0.5% to 1%, and in a specific embodiment, it can be 0.5% or 0.8%; the pickling method is immersion, and the time is 0.5 to 2 minutes, and in a specific embodiment, it can be 1 minute; the reagents used for ultrasonic cleaning are acetone, anhydrous ethanol and deionized water, and in a specific embodiment, acetone, anhydrous ethanol and deionized water cleaning can be performed in sequence; the single ultrasonic cleaning time is 20 to 30 minutes, and in a specific embodiment, it can be 25 minutes; the drying temperature is 40 to 60°C, and in a specific embodiment, it can be 50°C; the time is 1 to 2 hours, and in a specific embodiment, it can be 1.5 hours.
[0040] In the present invention, the magnetron sputtering further includes sequentially performing vacuuming, introducing argon gas and ion source cleaning; the vacuum degree of the vacuuming is ≤4×10 -4 Pa, in a specific embodiment, can be 4×10 -4 Pa; the flow rate of the introduced argon gas is 40 to 80 sccm, and in a specific embodiment, it can be 50 sccm or 70 sccm; the time for cleaning the ion source is 15 to 30 minutes.
[0041] In the present invention, the conditions of the magnetron sputtering include: a working pressure of 0.6 to 1.2 Pa, and in a specific embodiment, it can be 0.8 Pa or 1 Pa; a bias voltage of -50 to -150 V, and in a specific embodiment, it can be -100 V; the number of target positions is 2 to 4, and in a specific embodiment, it can be 3; the distance between the substrate and the composite target is 8 to 12 cm, and in a specific embodiment, it can be 9 cm or 11 cm; the magnetron sputtering uses a DC power supply, and the sputtering voltage is 200 to 500 V, and in a specific embodiment, it can be 300 V or 400 V; the sputtering current is 0.6 to 2 A, and in a specific embodiment, it can be 1 A or 1.5 A.
[0042] In the present invention, the temperature of the substrate is 350-650°C, and in a specific embodiment, it can be 400°C, 500°C or 600°C.
[0043] The preparation method of high entropy silicon boride provided by the present invention utilizes magnetron sputtering technology, uses a composite target formed by arranging and splicing multiple ceramic targets, and uniformly deposits a high entropy silicon boride coating on the surface of a substrate. The bonding force between the coating and the substrate is strong, and the coating and the substrate can still maintain a relatively tight bond at high temperatures.
[0044] The present invention also provides a SiC f / Ti3Al composite fasteners, including SiC f / Ti3Al composite fastener substrate and deposited on the SiC f / Ti3Al composite fastener substrate surface anti-oxidation coating; the material of the anti-oxidation coating is the high entropy silicon boride described in the above technical solution or the high entropy silicon boride obtained by the preparation method described in the above technical solution.
[0045] In the present invention, the thickness of the anti-oxidation coating is 2-5 μm, and in a specific embodiment, it can be 3 or 4 μm.
[0046] The present invention also provides the high entropy silicon boride described in the above technical solution, the high entropy silicon boride obtained by the preparation method described in the above technical solution, or the SiC f Application of Ti3Al composite fasteners in aerospace materials.
[0047] The present invention provides the high entropy silicon boride or SiC f There is no special limitation on the application process of Ti3Al / Ti3Al composite fasteners in aerospace materials, and the application process may be carried out in a manner familiar to those skilled in the art.
[0048] In order to further illustrate the present invention, the following is a SiC f The anti-oxidation coating of the Ti3Al composite fastener and the preparation method thereof are described in detail, but they should not be understood as limiting the scope of protection of the present invention.
[0049] Example 1
[0050] SiC f The SiC / Ti3Al composite fastener was immersed in a hydrofluoric acid solution for 0.5 min, taken out and dried, placed in an acetone solution, cleaned in an ultrasonic cleaner for 25 min, ultrasonicated in an anhydrous ethanol solution for 25 min, and finally ultrasonicated in deionized water for 20 min, and then placed in a drying oven at 50 °C for 1 h to obtain a clean SiC f / Ti3Al composite fasteners. f / Ti3Al composite fasteners are fixed on the sample rack in the middle of the coating room. Five 10mm×75mm×8mm rectangular small targets of ZrB2, NbSi2, MoSi2, WSi2, and ZrSi2 are placed one by one from top to bottom, with five small targets as a group, and a total of 3 groups are placed. 15 small targets are spliced into a large composite target, such as Figure 1 As shown, the purpose of doing so is to avoid uneven element content of the same target material sputtered at different positions of the sample holder. Then the composite target is installed on the target position. The magnetron sputtering device chamber has three target positions, and the target-substrate distance is adjusted to 10 cm.
[0051] The coating chamber is evacuated until the vacuum reaches 4×10 -4 Pa. Open the vent valve and let in argon. Set the gas flow rate to 60sccm and adjust the coating chamber pressure to 0.8Pa. The sample holder can rotate with the spindle while rotating. Figure 2 As shown, turn on the sample rotation switch, set the sample holder speed to 5r / min, and the spindle revolution speed to 2r / min. Turn on the ion source switch, adjust the argon flow rate to control the voltage at 800V, and clean for 20 minutes. After cleaning, readjust the argon flow rate to 60sccm, turn off the ion source switch, close the exhaust valve, and turn off the gas. Turn on the heating switch and raise the substrate temperature to 400℃. Wait until the vacuum degree in the coating chamber reaches 4×10 -4 After the deposition is completed, the DC power supply and bias are turned off, the gas is turned off, the gate valve is adjusted to the maximum, and the coating chamber is taken out after cooling to room temperature to obtain the SiC with deposited anti-oxidation coating. f / Ti3Al composite fasteners.
[0052] Example 2
[0053] SiC f The SiC / Ti3Al composite fastener was immersed in a hydrofluoric acid solution for 0.5 min, taken out and dried, placed in an acetone solution, cleaned in an ultrasonic cleaner for 25 min, ultrasonicated in an anhydrous ethanol solution for 25 min, and finally ultrasonicated in deionized water for 20 min, and then placed in a drying oven at 50 °C for 1 h to obtain a clean SiC f / Ti3Al composite fasteners. f / Ti3Al composite fasteners are fixed on the sample rack in the middle of the coating room. Five 10mm×75mm×8mm rectangular small targets of ZrB2, NbSi2, MoSi2, WSi2, and SiB6 are placed one by one from top to bottom. These five small targets form a group, and are placed in 3 groups in total. 15 small targets are spliced into a large composite target, such as Figure 1 As shown, the purpose of doing so is to avoid uneven element content of the same target material sputtered at different positions of the sample holder. Then the composite target is installed on the target position. The magnetron sputtering device chamber has three target positions, and the target-substrate distance is adjusted to 10 cm.
[0054] The coating chamber is evacuated until the vacuum reaches 4×10 -4 Pa. Open the vent valve and let in argon. Set the gas flow rate to 60sccm and adjust the coating chamber pressure to 0.8Pa. The sample holder can rotate with the spindle while rotating. Figure 2 As shown, turn on the sample rotation switch, set the sample holder speed to 5r / min, and the spindle revolution speed to 2r / min. Turn on the ion source switch, adjust the argon flow rate to control the voltage at 800V, and clean for 20 minutes. After cleaning, readjust the argon flow rate to 60sccm, turn off the ion source switch, close the exhaust valve, and turn off the gas. Turn on the heating switch and raise the substrate temperature to 400℃. Wait until the vacuum degree in the coating chamber reaches 4×10 -4 After the deposition is completed, the DC power supply and bias are turned off, the gas is turned off, the gate valve is adjusted to the maximum, and the coating chamber is taken out after cooling to room temperature to obtain the SiC with deposited anti-oxidation coating. f / Ti3Al composite fasteners.
[0055] Comparative Example 1
[0056] The Ti3Al sheet was polished on a polishing machine using sandpaper of 1000 mesh, 2000 mesh, 5000 mesh, and 6000 mesh in sequence until the surface was smooth and free of obvious scratches. The polished Ti3Al sheet was then soaked in a hydrofluoric acid solution for 0.5 min, taken out and dried, placed in an acetone solution, cleaned in an ultrasonic cleaner for 25 min, ultrasonicated in anhydrous ethanol solution for 25 min, and finally ultrasonicated in deionized water for 20 min, and then placed in a drying oven at 50 ° C for 1 h to obtain a clean Ti3Al sheet.
[0057] Comparative Example 2
[0058] SiC fThe SiC / Ti3Al composite fastener was immersed in a hydrofluoric acid solution for 0.5 min, taken out and dried, placed in an acetone solution, cleaned in an ultrasonic cleaner for 25 min, ultrasonicated in an anhydrous ethanol solution for 25 min, and finally ultrasonicated in deionized water for 20 min, and then placed in a drying oven at 50 °C for 1 h to obtain a clean SiC f / Ti3Al composite fasteners. f / Ti3Al composite fasteners are fixed on the sample rack in the middle of the coating room. Five rectangular small targets of ZrSi2, NbSi2, MoSi2, WSi2, and ZrSi2 are placed one by one from top to bottom. These five small targets form a group, and a total of 3 groups are placed repeatedly. 15 small targets are spliced into a large composite target, such as Figure 1 As shown, the purpose of doing so is to avoid uneven element content of the same target material sputtered at different positions of the sample holder. Then the composite target is installed on the target position. The magnetron sputtering device chamber has three target positions, and the target-substrate distance is adjusted to 10 cm.
[0059] The coating chamber is evacuated until the vacuum reaches 4×10 -4 Pa. Open the vent valve and let in argon. Set the gas flow rate to 60sccm and adjust the coating chamber pressure to 0.8Pa. The sample holder can rotate with the spindle while rotating. Figure 2 As shown, turn on the sample rotation switch, set the sample holder speed to 5r / min, and the spindle revolution speed to 2r / min. Turn on the ion source switch, adjust the argon flow rate to control the voltage at 800V, and clean for 20 minutes. After cleaning, readjust the argon flow rate to 60sccm, turn off the ion source switch, close the exhaust valve, and turn off the gas. Turn on the heating switch and raise the substrate temperature to 400℃. Wait until the vacuum degree in the coating chamber reaches 4×10 -4 After 30 0.5 Pa, open the vent valve, introduce argon gas, the gas flow rate is 60 sccm, and adjust the coating chamber pressure to 0.8 Pa. Set the bias voltage to -100 V, turn on the DC power supply for sputtering, adjust the sputtering voltage to 475 V, the sputtering current to 738 mA, and the sputtering time to 1 h. After the deposition is completed, turn off the DC power supply and bias voltage, turn off the gas, adjust the gate valve to the maximum, wait for the coating chamber to cool to room temperature, and then take it out to obtain the SiC with high entropy silicide coating deposited. f / Ti3Al composite fasteners.
[0060] Test Example 1
[0061] The SiC deposited with the anti-oxidation coating obtained in Examples 1 to 2 f / Ti3Al composite fastener sample, Ti3Al sheet sample obtained in comparative example 1, and SiC deposited with high entropy silicide coating obtained in comparative example 2 f / Ti3Al composite fastener samples were subjected to high temperature oxidation tests. The specific steps are as follows: Place the sample in a quartz crucible and place it in the middle of a tubular furnace to heat it evenly. Seal the tubular furnace port, close the vent valve, turn on the mechanical pump, set the tubular furnace heating program, and heat it to 800°C at a rate of 10°C / min. Then turn off the mechanical pump and open the vent valve. Keep warm at 800°C for 4 hours and then turn off the tubular furnace switch. Allow the sample to cool slowly to room temperature in the tubular furnace naturally, and then take out the sample for SEM characterization and analysis. See the cross-section and surface SEM images of the sample. Figures 3-4 , wherein a corresponds to corresponding example 1, b corresponds to corresponding example 2, c corresponds to example 1, and d corresponds to example 2.
[0062] Depend on Figures 3-4 It can be seen that an oxide layer with a thickness of 3.5 μm is formed on the surface of the Ti3Al sample obtained in Comparative Example 1, and a large amount of non-protective metal oxides exist in the oxide layer. There are also many cracks and pores on the surface of the sample, indicating that the Ti3Al sample has been severely oxidized at high temperature.
[0063] The thickness of the oxide layer formed on the surface of the high entropy silicide coating obtained in Comparative Example 2 is 117 nm, which is significantly lower than that in Comparative Example 1. During high-temperature oxidation, Si atoms in the high entropy silicide coating are preferentially oxidized to form a SiO2 oxide layer on the surface of the coating, which hinders the diffusion of oxygen into the coating. And this preferential oxidation reduces the generation of non-protective metal oxides and improves the compactness and integrity of the oxide layer. However, it can be found from the SEM image of the surface that there are still certain metal oxides on the surface of the coating, and there are pores between these oxides, which can provide channels for the diffusion of oxygen atoms.
[0064] The boron content in the high entropy borosilicate coating obtained in Example 1 is relatively small, and the thickness of the oxide layer after oxidation is 92nm. Compared with Comparative Example 2, the thickness of the oxide layer is further reduced, and there is less metal oxide on the surface, and the oxide layer is more dense. This shows that the introduction of a small amount of B element can improve the oxidation resistance of the high entropy silicide coating.
[0065] The boron content in the high entropy borosilicate coating obtained in Example 2 is higher than that in Example 1, and the thickness of the oxide layer after oxidation is 55nm. Compared with other comparative examples and embodiments, its oxide layer thickness is the lowest and the metal oxide on the surface is the least. The product of high-temperature oxidation of boron element, B2O3, can be combined with SiO2 glass to form a borosilicate (SiO2·B2O3) glass phase, which has low viscosity and high fluidity, and can not only form a continuous and dense oxide layer on the coating surface faster, but also repair cracks and holes generated on the coating surface during high-temperature oxidation.
[0066] Test Example 2
[0067] The SiC deposited with the anti-oxidation coating obtained in Examples 1 to 2 f SiC / Ti3Al composite fastener sample and the deposited high entropy silicide coating obtained in Comparative Example 2 f The samples of / Ti3Al composite fasteners were subjected to indentation test and SEM characterization analysis. The SEM images of the samples are shown in Figure 5 , wherein a corresponds to Example 2, b corresponds to Example 1, and c corresponds to Example 2.
[0068] Depend on Figure 5 It can be seen that there are relatively obvious radial cracks at the indentation on the surface of the coating of Comparative Example 1, indicating that the toughness of the high entropy silicide coating is average; there are almost no cracks at the indentation on the surface of the coating obtained in Example 1 and Example 2, indicating that the introduction of element B improves the toughness of the high entropy silicide coating.
[0069] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A high entropy silicon boride, characterized in that: Includes metal elements and non-metal elements; the metal elements include Zr, Nb, Mo and W; the non-metal elements include Si and B; The molar ratio of the metal element to the non-metal element is 1:1.5-2; The molar ratio of Zr, Nb, Mo and W is 5-40:5-40:5-40:5-40; The atomic content of B in the non-metallic element is 5 to 25 at.%.
2. The method for preparing high entropy silicon boride according to claim 1, characterized in that: The following steps are involved: In an argon environment, a composite target is deposited on a substrate surface by magnetron sputtering to obtain the high entropy silicon boride; the material of the composite target includes MoSi2, WSi2 and NbSi2, and also includes two or more of ZrSi2, ZrB2 and SiB6.
3. The preparation method according to claim 2, characterized in that: The composite target is composed of 3 to 5 groups of target materials; each group of target materials independently includes 5 to 6 small target materials; each group of target materials independently includes MoSi2 target, WSi2 target and NbSi2 target, and also includes more than two of ZrSi2 target, ZrB2 target and SiB6 target.
4. The preparation method according to claim 2, characterized in that: The conditions of the magnetron sputtering include: working pressure of 0.6Pa to 1.2Pa, bias voltage of -50 to -150V, number of target positions of 2 to 4, and distance between substrate and composite target of 8 to 12cm; the magnetron sputtering uses a DC power supply, sputtering voltage of 200 to 500V, and sputtering current of 0.6 to 2A.
5. The preparation method according to claim 2 or 4, characterized in that: The temperature of the substrate is 350-650°C.
6. A SiC f / Ti3Al composite fastener, characterized in that: Including SiC f / Ti3Al composite fastener substrate and deposited on the SiC f / Ti3Al composite fastener substrate surface anti-oxidation coating; the material of the anti-oxidation coating is the high entropy silicon boride described in claim 1 or the high entropy silicon boride obtained by the preparation method according to any one of claims 2 to 5.
7. The SiC according to claim 6 f / Ti3Al composite fastener, characterized in that: The thickness of the anti-oxidation coating is 2-5 μm.
8. The high entropy silicon boride according to claim 1, the high entropy silicon boride obtained by the preparation method according to any one of claims 2 to 5, or the SiC according to claim 6 or 7 f Application of Ti3Al composite fasteners in aerospace materials.
Citation Information
Patent Citations
In-situ synthesis method of high-entropy silicide film with anti-oxidation characteristic
CN113789503A
Superhard nano heterogeneous medium-entropy alloy film and preparation method thereof
CN115595542A
High-temperature oxidation-resistant high-entropy nitride film and preparation and application thereof
CN117187766A
High-performance high-entropy ceramic-based nano multilayer coating and preparation method thereof
CN118164783A
High-entropy alloys for covering components
EP3543368A1